Evaluation of Interleukin6 (IL-6) levels in Atopic Dermatitis Patients in Thi-Qar province - Naji, Amel A.; Mousa, Hind M (University of Thi-Qar Journal of Science, 2022)
IL-6 is a pro-inflammatory marker seen in the circulation of atopic disease. The study comprised 90 people of both genders, 45 of whom were patients, and the same number served as controls. Blood samples were obtained from both groups, and the serum levels of IL-6 were estimated using an IL-6 ECLIA kit by Electro-chemilumenescence Immunoassay. The findings of the present study referred that there were elevated sera levels of IL-6 (12.26pg/ml ) in AD patients in contrast to the control groups (4.05pg/ml) with a significant difference . Also, The results revealed an increase in the levels of IL-6 in severe AD patients compared with control group with highly statistically significant(P≤ 0.01). According to the results of the current study, it can be concluded that IL6 plays a critical role in the pathogenesis of dermatitis, and its elevated levels correlate with the clinical severity of the disease pathogenesis of AD